The Impact of Surgical Technique and Extent of Thyroidectomy in Voice Outcomes a Prospective Study - Jamshed Alam, Musarrat Hussain, Muhib Ullah, Muhammad Jawad Zahid, (Pakistan Journal of Medical & Health Sciences, 2023)
This prospective study aimed to evaluate the impact of surgical technique and extent of thyroidectomy on voice outcomes in 46 patients undergoing thyroidectomy. Patients were divided into three groups: limited thyroidectomy (n=20), total thyroidectomy (n=19), and extended thyroidectomy (n=7). Voice assessments were performed preoperatively and at 3 and 6 months postoperatively. Results showed that the surgical technique and extent of thyroidectomy had no significant effect on voice outcomes. However, a greater proportion of patients with limited thyroidectomy experienced a decrease in voice quality at three months postoperatively compared to patients with total or extended thyroidectomy. This study suggests that surgical technique and extent of thyroidectomy do not significantly affect voice outcomes in the long term. Further research is needed to understand these factors' impact on voice outcomes. Methodology: This prospective study was conducted in the department of surgery hmc Peshawar from Jan 2020 to Jan 2021 over the 01 years of a pride sample size of 46 patients (30 male and 16 female) who underwent thyroidectomy. Patients were divided into three groups based on the surgical technique and extent of thyroidectomy: limited thyroidectomy (n=20), total thyroidectomy (n=19), and extended thyroidectomy (n=7). All patients underwent preoperative and postoperative voice assessments at 3 and 6 months. The assessments included acoustic analysis and perceptual evaluation of voice quality. Results were compared between the three groups to evaluate the surgical technique's impact and thyroidectomy's extent on voice outcomes. Statistical analysis was performed to analyze the data. Results: The results showed that the surgical technique and extent of thyroidectomy had no significant effect on voice outcomes. However, a greater proportion of patients with limited thyroidectomy experienced a decrease in voice quality at three months postoperatively, compared to patients with total or extended thyroidectomy results shown in tables 1 to 7. Conclusion: This study suggests that surgical technique and extent of thyroidectomy do not significantly affect voice outcomes in the long term. Further research is needed to understand these factors' impact on voice outcomes. keywords: thyroidectomy, voice outcomes, surgical technique, the extent of thyroidectomy